2015
DOI: 10.1002/joc.4458
|View full text |Cite
|
Sign up to set email alerts
|

Observed urban effects on precipitation along the Dutch West coast

Abstract: Expansion of urban areas has profound effects on land surface characteristics. As such, the land surface can exert influence on atmospheric parameters that might alter precipitation amounts or patterns. In this study, precipitation observations near urban areas along the West coast of the Netherlands are investigated throughout the 1951-2010 period. An innovative analysis methodology is used to deal with the small and fragmented urban areas in the Netherlands. The results show that daily precipitation totals d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…The overall features of the hourly precipitation analysis reveal greater values in cities than in the countryside, and the highest precipitation difference in the summer. The observed enhanced cumulative precipitation in urban areas is in agreement with the previous study on the urbanisation impacts on urban climates by Daniels et al (2015), which showed a 7% enhancement of precipitation in Dutch cities. Thus, we confer further confidence to the recorded observations of the amateur stations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The overall features of the hourly precipitation analysis reveal greater values in cities than in the countryside, and the highest precipitation difference in the summer. The observed enhanced cumulative precipitation in urban areas is in agreement with the previous study on the urbanisation impacts on urban climates by Daniels et al (2015), which showed a 7% enhancement of precipitation in Dutch cities. Thus, we confer further confidence to the recorded observations of the amateur stations.…”
Section: Discussionsupporting
confidence: 92%
“…The urbanization and population average growth rates (0.77% and 1.05%, respectively) between 2010 and 2015 indicate a fairly rapid urbanization in The Netherlands (Un 2015). Although there has been a continuous urbanization in The Netherlands (Hazeu et al 2011, Daniels et al 2015, long-term meteorological observations are scarce for Dutch cities (for more details, see Van Hove et al 2011). The study presented here attempts to investigate the temperature and precipitation variations using citizens' personal amateur weather stations (PWS) to understand the urban environments of a number of Dutch cities (Jiang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that the downwind effects of urban areas on precipitation in the Netherlands are largest under WT9 (Daniels et al, 2015b). Under the light, unclassifiable, flow that occurs in this weather type, the atmosphere seems to be most susceptible to the land surface.…”
Section: Case Selectionmentioning
confidence: 97%
“…The increase in sea surface temperatures and changes in circulation seem to be the major causes of this increase (Attema et al, 2014;van Haren et al, 2013). In addition, there is some evidence that urbanization plays a role (Daniels et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation